On the Use of Crowdsourcing Labor Markets in Research. Issue 2 (June 2016) - Marinova, Dani M.
Abstract : Crowdsourcing platforms offer a source of inexpensive data for research. At their fingertips, researchers have a round-the-clock workforce to fill out surveys, participate in experiments, and content-analyze text, among other tasks that generate social science data and help support research. Thanks to its low cost and convenience, crowdlabor has quickly and uncritically become a mainstream tool in our discipline. While such platforms have been evaluated on their aptness to generate high-quality data, surprisingly little has been said about the economic or political implications of their usage. Among other aspects, this article problematizes the "state of legal exception" in which crowdlabor markets operate, their tendency to rely on a pool of economically vulnerable workers and the asymmetrical employment relations they create. Rather than offer an easy solution, I aim to open up a conversation about this unique set of challenges in order to acknowledge and address them.